2015
DOI: 10.1080/17470218.2014.979212
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to instructed reversal of the learned predictiveness effect

Abstract: The learned predictiveness effect is a widely observed bias towards previously predictive cues in novel situations. Although the effect is generally attributed to an automatic attentional shift, it has recently been explained as the product of controlled inferences about the predictive value of cues. This view is supported by the susceptibility of learned predictiveness to instruction manipulation. However, recent research has shown conflicting results. Three experiments investigated the parameters of the inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 30 publications
4
36
1
Order By: Relevance
“…In line with previous evidence [10, 13, 14], we found that participants’ learning of stimulus-outcome relationships during Phase 2 was influenced by instructions regarding relevance: Participants learned more, in general, about stimuli instructed as relevant than those that were not instructed. That said, the influence of instructions on learning was relatively slight, and was not sufficient to overcome the influence of experienced predictiveness on learning.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with previous evidence [10, 13, 14], we found that participants’ learning of stimulus-outcome relationships during Phase 2 was influenced by instructions regarding relevance: Participants learned more, in general, about stimuli instructed as relevant than those that were not instructed. That said, the influence of instructions on learning was relatively slight, and was not sufficient to overcome the influence of experienced predictiveness on learning.…”
Section: Discussionsupporting
confidence: 91%
“…The design of our study was conceptually similar to that of Mitchell et al [10] in that it compared the influence of training versus instruction on predictiveness-related attentional biases. Our study departed from the procedure of Mitchell et al by using a within-subjects manipulation of verbal instructions, in order to increase the sensitivity of the experiment (a similar approach was used in Don & Livesey’s, Experiment 3 [13], and in Shone et al’s Experiment 2 [14]). Accordingly, after Phase 1, participants were informed that four specific stimuli would be the most relevant to learn about during Phase 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, more was learned about previously non-predictive cues than previously predictive cues in Phase 2. Subsequent studies have partially replicated this sensitivity to instructions, though have typically found much weaker instructed reversal effects accompanied by a continued influence of biases established in Phase 1, despite clear evidence that the participants have read and understood the instructions (Don and Livesey, 2015; Shone et al, 2015). While Mitchell et al (2012) favored an explanation purely based on conscious reasoning processes, where participants deliberately attend to the cues they believe are important, a viable alternative is that attentional processes are brought under conscious control and thus let non-associative knowledge influence the course of subsequent learning.…”
Section: How Might Non-associative Knowledge Influence An Associativementioning
confidence: 98%
“…Work on the learned predictiveness effect clearly demonstrates an effect of instructed attention on selective learning (Mitchell et al, 2012; Don and Livesey, 2015; Shone et al, 2015). The learned predictiveness effect is a widely observed learning bias toward previously predictive cues in novel situations (see Le Pelley et al, 2016 for a recent review).…”
Section: How Might Non-associative Knowledge Influence An Associativementioning
confidence: 99%